Farmers' preferences for livestock pollution control policy in China: a choice experiment method. (10th September 2016) - Pan, Dan; Zhou, Guzhen; Zhang, Ning; Zhang, Liguo
Abstract: Using a survey data of 754 pig breeders in China, the choice experiment method was employed to investigate farmers' preferences for livestock pollution control policy. Five attributes—technical support, pollution fees, technical standards, biogas subsidies, and the manure market—were set as parameters of a study of livestock pollution control policies. A random parameter logit model was used, which considered the heterogeneity of the farmers' preferences. The main results are as follows: (i) the biogas subsidy, technical support, pollution fees and manure market were shown to be significant factors of preference—over alternative policy designs—in terms of incremental changes in environmentally-friendly manure handling; (ii) heterogeneity was observed in farmers' preferences for livestock pollution control policies. Farmers' choices of improved pollution policy options were significantly influenced by their education, the size of their farms and their willingness to treat pollution; (iii) farmers showed the highest preferences for a biogas subsidy policy, followed (in this order) by a high technical support policy, a pollution fee policy, a medium technical support policy, a manure market policy and finally a technical standard policy.